2003
DOI: 10.1002/ana.10996
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal cord stimulation in patients with chronic reflex sympathetic dystrophy: Two years' follow‐up of the randomized controlled trial

Abstract: Chronic reflex sympathetic dystrophy is a painful, disabling disorder for which no treatment with proven effect is available. We performed a randomized trial in a 2 to 1 ratio of patients, in which 36 patients were treated with spinal cord stimulation and physical therapy (SCS+PT), and 18 patients received solely PT. Twenty-four SCS+PT patients were given a permanent spinal cord stimulation system after successful test stimulation; the remaining 12 patients received no permanent system. We assessed pain intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
0
20

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 28 publications
(32 reference statements)
8
169
0
20
Order By: Relevance
“…The most typical example of such pain is Complex Regional Pain Syndrome (CRPS) of both types, which is known to have a relatively high likelihood of responding to SCS. 38 There are several studies demonstrating that the efficacy of SCS is related to the temporary outcome of sympathetic blockades, i.e., stellate, lumbar sympathetic blocks, or regional guanethidine blocks. 39 However, there are also studies reporting that also patients who have failed to respond to sympathetic block may benefit from SCS.…”
Section: Pain With Dysautonomiamentioning
confidence: 99%
“…The most typical example of such pain is Complex Regional Pain Syndrome (CRPS) of both types, which is known to have a relatively high likelihood of responding to SCS. 38 There are several studies demonstrating that the efficacy of SCS is related to the temporary outcome of sympathetic blockades, i.e., stellate, lumbar sympathetic blocks, or regional guanethidine blocks. 39 However, there are also studies reporting that also patients who have failed to respond to sympathetic block may benefit from SCS.…”
Section: Pain With Dysautonomiamentioning
confidence: 99%
“…In terms of the neuropathic pain etiology, SCS has been applied in the treatment of deafferentation pain, central pain, phantom limb pain (PLP), causalgia, myelopathy, oncologic pain, lumbosacral fibrosis, postherpetic neuralgia (PHN), FBSS, CRPS, reflex sympathetic dystrophy (RSD), spinal cord, brainstem or brain injury, and others (3,(13)(14)(15)22,32,33,38,42,43,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Results In Pain Managementmentioning
confidence: 99%
“…• Patients with medical intractability of neuropathic pain (20,22,26,32,38,(45)(46)(47)(48)(49) During the surgical procedure of trial implantation, patients should be asked to indicate the location of parenthesis (change of sensibility correlated to the spinal segment stimulated) since it is relevant to confirm that the resultant parenthesis overlaps with the painful area to achieve good analgesia (20)(21)(22)26,28,45).…”
Section: Selection Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Kemler et al [24] examined the effects of SCS with physiotherapy compared to physical therapy alone in patients with CRPS type I. They reported that at the 6 month follow-up, the mean decrease in pain score was 2.4 with SCS compared to 0.4 with physical therapy using the visual analog scale (VAS) from 0 (no pain) to 10 (worst possible pain).…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%